Surface Modification of Polypropylene Membrane Using Biopolymers with Potential Applications for Metal Ion Removal - Omar Alberto Hernández-Aguirre; Alejandra Núñez-Pineda; Melina Tapia-Tapia; Rosa María Gómez Espinosa (Journal of Chemistry)
This work aims to present the modification of polypropylene (PP) membranes using three different biopolymers, chitosan (CHI), potato starch (PS), and cellulose (CEL), in order to obtain three new materials. The modified membranes may be degraded easier than polypropylene ones and could be used as selective membranes for metal ions removal, among other applications. For this purpose, the UV energy induced graft copolymerization reaction among polypropylene membrane, acrylic acid, benzophenone (as photoinitiator), and the biopolymer (CHI, PS, or CEL) was conducted. The results of FT-IR-ATR, XRD, TGA, DSC, SEM, BET, and AFM analyses and mechanical properties clearly indicate the successful modification of the membrane surface. The change of surface wettability was monitored by contact angle. The grafting reaction depends on natural polymer, reaction time, and concentration. In order to prove the potential application of the modified membranes, a preliminary study of sorption of metal ion was carried out. For this purpose, the PP-CHI membrane was chosen because of the high hydrophilicity, proportionate to -OH and NH2; these groups could act as ligands of metal ions, provoking the interaction between PP-CHI and M+ (PP-CHI-M+) and therefore the metal ion removal from water.